2003
DOI: 10.4049/jimmunol.170.11.5697
|View full text |Cite
|
Sign up to set email alerts
|

IL-1α, Innate Immunity, and Skin Carcinogenesis: The Effect of Constitutive Expression of IL-1α in Epidermis on Chemical Carcinogenesis

Abstract: Tumor promoters such as the phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA) are proinflammatory agents, and their mechanism of action in epithelial carcinogenesis has been linked to the release of IL-1α and the induction of chronic inflammation in skin. To test the role of IL-1α and inflammation in models of cutaneous carcinogenesis, we used our previously described FVB/N transgenic mice overexpressing 17-kDa IL-1α in the epidermis under the keratin 14 (K14) promoter. Strikingly, the K14/IL-1α mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 42 publications
1
56
0
4
Order By: Relevance
“…TNF-a-induced MMP-9 protein expression was significantly decreased by neutralization of avb6 compared with control (b; asterisk denotes P ¼ 0.0022). Data are representative of at least two independent experiments response of the skin to injury (Murphy et al, 2003). Little is known regarding the precise role of TNF-a during wound healing and conflicting evidence exists in the literature (Buck et al, 1996;Hubner et al, 1996;Lee et al, 2000;Mori et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a-induced MMP-9 protein expression was significantly decreased by neutralization of avb6 compared with control (b; asterisk denotes P ¼ 0.0022). Data are representative of at least two independent experiments response of the skin to injury (Murphy et al, 2003). Little is known regarding the precise role of TNF-a during wound healing and conflicting evidence exists in the literature (Buck et al, 1996;Hubner et al, 1996;Lee et al, 2000;Mori et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, resorcinol, which was negative in the rat and mouse NTP bioassay, induced papillomas in Tg.AC mice when given at a level that also caused inflammation in the skin (Sistare et al, 2002). However, investigations into the role of inflammation in tumorigenesis in Tg.AC mice have also produced contradictory results, necessitating further research (Albert et al, 1996;Murphy et al, 2003). Tumor development in SEPA 0009-treated Tg.AC mice, which is preceded by a severe and chronic skin irritation, is consistent with the response of Tg.AC mice to sustained irritation and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Moore et al (1999) reported that proinflammatory cytokines were important for de novo carcinogenesis and mice deficient in TNF-α are resistant to skin carcinogenesis. However, constitutive expression of IL-1α in the epidermis of FVB mice rendered them completely resistant to skin carcinogenesis (Murphy et al, 2003).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Moore et al (1999) reported that proinflammatory cytokines were important for de novo carcinogenesis and mice deficient in TNF-α are resistant to skin carcinogenesis. However, constitutive expression of IL-1α in the epidermis of FVB mice rendered them completely resistant to skin carcinogenesis (Murphy et al, 2003).Studies from our laboratory have demonstrated that topical application of DMBA, B(a)P and 3-methylcholanthrene (3-MC) -three carcinogenic polyaromatic hydrocarbons -results in the induction of a contact hypersensitivity response, which is a T-cell-mediated immune response to topically applied haptens (Figure 1) (Klemme et al, 1987;Anderson et al, 1995). The response fulfills all of the requirements of an acquired immune response including antigen specificity and the ability to be adoptively transferred with cell suspensions from draining lymph nodes (Klemme et al, 1987).…”
mentioning
confidence: 99%